2000
DOI: 10.1161/01.cir.102.23.2810
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin Tolerance in Human Vessels

Abstract: Background-The basis for progressive attenuation of the effects of organic nitrates during long-term therapy (nitrate tolerance) remains controversial; proposed mechanisms include impaired nitrate bioconversion resulting in decreased release of nitric oxide (NO) from nitrates and/or increased NO clearance through a reaction with incrementally generated superoxide (O 2 -). Methods and Results-Patients undergoing elective coronary artery bypass were randomized to receive 24 hours of intravenously infused nitrogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(43 citation statements)
references
References 32 publications
3
39
1
Order By: Relevance
“…Consistent with this observation is the report that aldehyde dehydrogenase activity is markedly inhibited in patients undergoing chronic administration of nitroglycerin and other organic nitrate esters (20). These findings also are consistent with previous reports that nitroglycerin tolerance in patients can sometimes be overcome by administration of N-acetylcysteine (5,21).…”
supporting
confidence: 91%
“…Consistent with this observation is the report that aldehyde dehydrogenase activity is markedly inhibited in patients undergoing chronic administration of nitroglycerin and other organic nitrate esters (20). These findings also are consistent with previous reports that nitroglycerin tolerance in patients can sometimes be overcome by administration of N-acetylcysteine (5,21).…”
supporting
confidence: 91%
“…Long-term administration of nitrates causes nitrate tolerance or tachyphylaxis in many species including man [4,5,7,8,10,11]. Recently, there has been a strong focus on a proposed free radical hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate tolerance or tachyphylaxis is characterized by a reduction in the nitrate-induced cyclic GMP-mediated pathway [4]. Proposed mechanisms of tolerance include: (1) depletion of critical sulfhydryl groups [5], (2) desensitization of guanylyl cyclase [6], (3) impaired bioconversion of nitrates leading to diminished NO-release [7], (4) reduced generation of NO from nitrates [8], (5) increased activity of the cyclic GMP phosphodiesterase, which decreases cyclic GMP levels [9] and (6) a free radical hypothesis proposing increased oxidant stress [10,11]. Nitroglycerininduced reactive oxygen species also inhibit the activation of nitroglycerin by thiol oxidation of mitochondrial aldehyde dehydrogenase which might explain why nitroglycerin elicits mitochondrial superoxide formation and nitrate tolerance [12].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, all organic nitrates are potentially prone to the development of nitrate tolerance during long-term therapy: this is manifest as progressive attenuation of hemodynamic and anti-aggregatory responses to the administered nitrate, with cross-tolerance to other organic nitrates. While some investigators have suggested that nitrate tolerance is also associated with worsening of endothelial dysfunction and attenuation of responsiveness to endogenous NO (that is, cross-tolerance to endothelial NO), overall evidence is more consistent with the concept that nitrate tolerance is engendered primarily by failure of enzymatic release of NO from organic nitrates (Sage et al, 2000). As the probability of emergence of nitrate tolerance is determined essentially by the combination of infusion rate and duration of exposure (Henry et al, 1989), this imposes the need to utilize organic nitrate infusions briefly and with the lowest possible infusion rates.…”
Section: Mechanisms Of Nitrite-mediated Vasodilatationmentioning
confidence: 86%
“…The relative selectivity for the (hypoxic) venous capacitance vessels and pulmonary vasculature would be an attractive profile in the management of decompensated heart failure. Furthermore the apparent lack of tolerance (Haas et al, 1999;Dejam et al, 2007) would be an additional advantage over organic nitrates (Sage et al, 2000). However sustained high dose nitrite infusion can cause methemoglobinemia and hemolysis (Pluta et al, 2011).…”
Section: Mechanisms Of Nitrite-mediated Vasodilatationmentioning
confidence: 99%